Parallelepipeds are of Equal Volume iff Bases are in Reciprocal Proportion to Heights
Theorem
In the words of Euclid:
- In equal parallelepidedal solids the bases are reciprocally proportional to the heights; and those parallelepidedal solids in which the bases are reciprocally proportional to the heights are equal.
(The Elements: Book $\text{XI}$: Proposition $34$)
Proof
Let $AB$ and $CD$ be equal parallelepipeds.
It is to be demonstrated that the bases of $AB$ and $CD$ are inversely proportional to their heights.
That is:
- $EH : NQ = CM : AG$
First, let $AG, EF, LB, HK, CM, NO, PD, QR$ be perpendicular to their bases.
It is to be shown that:
- $EH : NQ = CM : AG$
Suppose $EH = NQ$.
- $CM = AG$
Thus it follows trivially that:
- $EH : NQ = CM : AG$
Next, suppose $EH \ne NQ$.
Suppose WLOG that $EH > NQ$.
We have that $AB = CD$.
Therefore $CM > AG$.
Let $CT = AG$.
Let the parallelepiped $CV$ be completed on the base $NQ$ and with height $CT$.
We have that $AB = CD$.
So from Proposition $7$ of Book $\text{V} $: Ratios of Equal Magnitudes:
- $AB : CV = CD : CV$
- $AB : CV = EH : NQ$
From Proposition $25$ of Book $\text{XI} $: Parallelepiped cut by Plane Parallel to Opposite Planes:
- $CD : CV = MQ : TQ$
and from Proposition $1$ of Book $\text{VI} $: Areas of Triangles and Parallelograms Proportional to Base:
- $CD : CV = CM : CT$
Therefore also:
- $EH : NQ = MC : CT$
But:
- $CT = AG$
Therefore also:
- $EH : NQ = MC : AG$
Therefore in the parallelepipeds $AB$ and $CD$, the bases are inversely proportional to their heights.
$\Box$
Now let the bases of the parallelepipeds $AB$ and $CD$ be inversely proportional to their heights.
That is:
- $EH : NQ = MC : AG$
It is to be shown that $AB = CD$.
Let the sides $AG, EF, LB, HK, CM, NO, PD, QR$ be perpendicular to their bases.
Let $EH = NQ$.
Then it follows from $EH : NQ = MC : AG$ that $MC = AG$.
- $AB = CD$
Next suppose that $EH \ne NQ$.
Suppose WLOG that $EH > NQ$.
Therefore the height of $CD$ is greater than the height of $AB$.
That is:
- $CM > AG$
Let $CT = AG$.
Let the parallelepiped $CV$ be completed on the base $NQ$ and with height $CT$.
We have that:
- $EH : NQ = MC : AG$
while:
- $AG = CT$
Therefore:
- $EH : NQ = CM : CT$
We have that $AB$ and $CV$ are of equal height.
- $EH : NQ = AB : CV$
From Proposition $1$ of Book $\text{VI} $: Areas of Triangles and Parallelograms Proportional to Base:
- $CM : CT = MQ : QT$
and from Proposition $25$ of Book $\text{XI} $: Parallelepiped cut by Plane Parallel to Opposite Planes:
- $CM : CT = CD : CV$
Therefore also:
- $AB : CV = CD : CV$
Therefore from Proposition $9$ of Book $\text{V} $: Magnitudes with Same Ratios are Equal:
- $AB = CD$
$\Box$
Now let $AG, EF, LB, HK, CM, NO, PD, QR$ not be perpendicular to their bases.
Let perpendiculars be drawn from $F, G, B, K, O, M, D, R$ to the planes through $EH$ and $NQ$, meeting them at $S, T, U, V, W, X, Y, A'$.
Let the parallelepipeds $FV$ and $OA'$ be completed.
We have that:
- $AB = CD$
We have that $AB$ and $BT$ are on the same base $FK$ and have the same height.
From:
and:
we have that:
- $AB = BT$
For the same reason:
- $CD = DX$
Therefore:
- $BT = DX$
Therefore from the first part of this result:
But:
- $FK = EH$
and:
- $OR = NQ$
Therefore:
But $DX$ and $BT$ have the same heights respectively as $DC$ and $BA$.
Therefore:
Therefore in the parallelepipeds $AB$ and $CD$, the bases are inversely proportional to their heights.
$\Box$
Now let the bases of the parallelepipeds $AB$ and $CD$ be inversely proportional to their heights.
Let perpendiculars be drawn from $F, G, B, K, O, M, D, R$ to the planes through $EH$ and $NQ$, meeting them at $S, T, U, V, W, X, Y, A'$.
Let the parallelepipeds $FV$ and $OA'$ be completed.
Then as $DY$ and $BU$ are the heights of $AB$ and $CD$:
- $EH : NQ = DY : BU$
Thus:
We have:
- $EH = FK$
and:
- $NQ = OR$
Therefore:
But $AB$ and $CD$ have the same heights as $BT$ and $DX$ respectively.
Therefore:
Therefore the bases of the parallelepipeds $BT$ and $DX$ are inversely proportional to their heights.
Therefore by the first part of this result:
- $BT = DX$
But from:
and:
we have that:
- $AB = BT$
and:
- $DX = DC$
Therefore:
- $AB = CD$
$\blacksquare$
Historical Note
This proof is Proposition $34$ of Book $\text{XI}$ of Euclid's The Elements.
Sources
- 1926: Sir Thomas L. Heath: Euclid: The Thirteen Books of The Elements: Volume 3 (2nd ed.) ... (previous) ... (next): Book $\text{XI}$. Propositions